NEEDS ANALYSIS AS A MAIN PHASE FOR DESIGNING ENGLISH FOR SPECIFIC PURPOSES (ESP) COURSE - Mamatqulova Marhabo, (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
This article is based on Needs Analysis of the third-year students who are studying in the direction of Hotel and Tourism Management in Kokand University. The field of Tourism is now widely considered as one of the most important languages in discourse of tourism, serving as the basis for forming and developing worldwide professional tourism relationships throughout the globe. For teaching English to tourism students, it is not required a strictly set policy, however, various syllabus or curriculum based on particular field of Tourism can be employed in other institutions to assist the students to achieve their intended goals. In order to know the needs of students, direct and indirect approaches as well as unstructured interview, writing and a questionnaire are applied.